EP-368 Intraoperative identification of colorectal cancer lesions using indocyanine green labelled antibodies in preclinical murine models. (9th August 2022) - Lyons, Nicholas; Hooper, John; Clark, David; Riddell, Andrew; Kryza, Thomas
Abstract: Aims: The ability to identify cancerous tissue intraoperatively has the potential to allow for real time identification of involved margins, lymph node involvement and extra-colonic deposits. Here we investigate whether antibodies targeting a novel receptor, anonymously referred to as LN1, a frequently over expressed protein in colorectal cancer (CRC), labelled with indocyanine green (ICG) can be used for the intraoperative detection of malignant tissue in preclinical models. Methods: Representative metastatic CRC models were generated in 20 NSG mice using HCT116 human CRC cells. Mice were treated with either intravenous ICG labelled LN1 antibodies (LN1-ICG) or control treatments (untreated, free ICG or cotreatment unlabelled LN1 blocking antibody + LN1-ICG). Signal intensity of normal and malignant tissue was quantified from near infrared (NIR) endoscopy and IVIS® in-vivo imaging system. Results: LN1-ICG labelled antibodies was highly effective in identifying cancerous lesions down to 500nm diameter. Quantification of NIR and IVIS images demonstrate significantly greater tumour signal in the LN1-ICG group versus controls (p=0.004 and p=0.001 respectively). Examination of normal organ tissues demonstrated signal in the liver and digestive tract in keeping with hepatobiliary clearance of ICG but nil further off-site accumulation of LN1-ICG. No difference in signal from the liver, small bowel or colon was noted between groups (p>0.05). Conclusion: LN1-ICG labelled antibodies were highly effective at identifying even small cancerous deposits in murine models. It is highly likely that these effects could be replicated in human procedures which may allow for perioperative identification of extra-colonic deposits, involved tumour margins or lymph node involvement.